Hypertension and Serum C-Reactive Protein Levels in Pre-eclampsia - Ruma, Kazi Sadeka; Rashed, Begum Sultana Hasina; Ferdous, Jannatul; Akhter, Tanvina; Maksurat, Farjana; Urmy, Nushrat Jahan (Community Based Medical Journal, 2026)
A case-control study was carried out in the Department of Obstetrics & Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between January 2013 and June 2014, to see the association of hypertension and C-reactive protein (CRP) levels in pre-eclampsia patients. A total of 78 patients were enrolled in the study. Patients were divided into three groups: group-I included of 26 pregnant women with mild pre-eclampsia, while group-II had 26 pregnant women with severe pre-eclampsia and group-III had 26 women with normal pregnancy. Group-I and group-II were together considered as ‘case’, while group-III was considered as ‘control’. We adopted a convenient sampling technique. For each patient, after a 10-minute of resting phase, blood pressure was measured following standard procedure. C-reactive protein (CRP) was measured from patients’ serum based on latex particle-enhanced nephelometric immunoassay using CardioPhase® High Sensitivity CRP kit. The mean systolic BP was found 155.0±13.7 mmHg in group-I+group-II (case group) (i.e., mild and severe pre-eclampsia), while 108.46±0.8 mmHg in group III (control group). Similarly, the mean diastolic BP was found 102.31±9.7 mmHg in group-I+group-II and 68.46±7.8 mmHg in group-III. The differences were statistically significant (p=0.001). The mean CRP level was found 23.82±21.8 mg/L in group-I+group-II (case group) and 4.42±0.9 mg/L in group-III (control group). The difference was statistically significant (p=0.001). A positive significant correlation was found between systolic blood pressure and CRP level, as of Pearson's correlation coefficient r=0.439 (p=0.025) and r=0.434 (p=0.027) in mild and severe pre-eclampsia respectively. Similarly, a positive significant correlation was found between diastolic blood pressure and CRP level, as of Pearson's correlation coefficient r=0.446 (p=0.022) and r=0.440 (p=0.024) in mild and severe pre-eclampsia respectively. CBMJ 2026 January: vol. 15 no. 01 P:50-55